Digestive enzyme activities in mudskipper Boleophthalmus pectinirostris and Chinese black sleeper Bostrichthys sinensis - 吴仁协 洪万树 张其永 (Chinese journal of oceanology and limnology, 2010)
The mudskipper Boleophthalmus pectinirostris and Chinese black sleeper Bostrichthys sinensis occupy the intertidal zone.However,both species have their own unique diet.The former is an herbivore and the latter is a carnivore.In order to reveal the relationship between digestive enzyme activities and diets in the two species,the activities of protease（P）,non-specific bile salt-activated lipase（BAL） and α-amylase（A） were determined in the stomach and intestine of adult mudskipper B.pectinirostris and Chinese black sleeper B.sinensis.The results showed that the activities of protease,BAL and α-amylase in the intestine of B.pectinirostris were significantly（P〈0.05） higher than those in the stomach.In B.sinensis,gastric protease activity was not different from the intestinal protease（P〉0.05）,while BAL and α-amylase activities of the intestine were significantly（P〈0.05） higher than those of the stomach.The activity of gastric protease in B.sinensis was significantly（P〈0.05） higher than that in B.pectinirostris,while the activities of intestinal protease were not different between the two fish species（P〉0.05）.BAL activities of the stomach and intestine in B.sinensis were significantly（P〈0.05） higher than those in B.pectinirostris,while α-amylase activities of the stomach and intestine in B.pectinirostris were significantly（P〈0.05） higher than those in B.sinensis.The ratios of P/BAL,A/P and A/BAL of the digestive tract in B.pectinirostris were 1.5,107.3 and 158.6,respectively; and those in B.sinensis were 0.2,1.6 and 0.2,respectively.It can be concluded that food digestion in the adult B.pectinirostris is mainly carried out in the intestine,whereas in the adult B.sinensis it is initiated in the stomach and finishes in the intestine.The activities of BAL and α-amylase in B.pectinirostris and B.sinensis are well correlated with their diets.However,a clear-cut correlation between protease activity and diets is not found in these two species.